African swine fever viruses with two different genotypes, both of which occur in domestic pigs, are associated with ticks and adult warthogs, respectively, at a single geographical site - Gallardo, C.; Okoth, S.; Pelayo, V.; Anchuelo, R.; Martin, E.; Simon, A.; Llorente, A.; Nieto, R.; Soler Garzón, Alvaro; Martin, R.; Arias, Marisa; Bishop, Richard P. (Microbiology Society, 2011)
The role of the ancestral sylvatic cycle of the African swine fever virus (ASFV) is not well understood in the endemic areas of eastern Africa. We therefore analysed the ASF infection status on samples collected from 51 free-ranging warthogs (Phacocherus africanus) and 1576 Ornithodorus porcinus ticks from 26 independent warthog burrows at a single ranch in Kenya. Abattoir samples from 83 domestic pigs without clinical symptoms, originating from specific locations with no recent reported ASF outbreaks were included in this study. All samples were derived from areas of central Kenya, where ASF outbreaks have been reported in the past. Infection with ASFV was confirmed in 22% of O. porcinus pools, 3.22% of adult warthog serum samples and 49% of domestic pig serum samples by using p72-based PCR. All of the warthog sera were positive for anti-ASFV antibodies, investigated by using ELISA, but none of the domestic pig sera were positive. Twenty O. porcinus-, 12 domestic pig- and three warthogderived viruses were genotyped at four polymorphic loci. The ASFV isolates from ticks and domestic pigs clustered within p72 genotype X. By contrast, ASF viruses genotyped directly from warthog sera, at same locality as the tick isolates, were within p72 genotype IX and genetically similar to viruses causing recent ASF outbreaks in Kenya and Uganda. This represents the first report of the co-existence of different ASFV genotypes in warthog burrow-associated ticks and adult wild warthogs. The data from this and earlier studies suggest transfer of viruses of at least two different p72 genotypes, from wild to domestic pigs in East Africa.